Benefits versus risk profile of buparlisib for the treatment of breast cancer. Issue 7 (3rd July 2019) - Patsouris, Anne; Augereau, Paule; Frenel, Jean-Sebastien; Robert, Marie; Gourmelon, Carole; Bourbouloux, Emmanuelle; Berton-Rigaud, Dominque; Chevalier, Louise-Marie; Campone, Mario
ABSTRACT: Introduction : Activation of phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathways occurs in 70% of breast cancer, including PIK3CA activating mutations, PTEN loss and AKT mutation. It is associated with poor prognosis and resistance to anti-HER2 and endocrine therapy. PI3K inhibitors are promising anticancer targets that can reverse resistance to these therapies. Buparlisib (BKM-120) is an orally active pan-PI3K inhibitor evaluated in different solid tumors as monotherapy or in combination. Areas covered : This article reviews preclinical data, clinical studies that have evaluated the efficacy and safety profiles of buparlisib as a monotherapy or in combination with targeted therapy (including endocrine and anti-HER2 therapy) or cytotoxics. The authors cover completed and ongoing studies to evaluate the benefit vs risk profile of buparlisib. Expert opinion : Targeting PI3K showed efficacy in BC. Buparlisib, a pan PI3K inhibitor, presents manageable but not negligible toxicity with an activity/toxicity ratio in favor of the use of emerging second generation, α–selective PI3K inhibitors for ongoing and future trials.